Root caries on a Paranthropus robustus third molar from Drimolen. Issue 2 (2nd July 2019) - Towle, Ian; Riga, Alessandro; Irish, Joel D.; Dori, Irene; Menter, Colin; Moggi‐Cecchi, Jacopo
Abstract: Objectives: Dental caries is often perceived as a modern human disease. However, their presence is documented in many early human groups, various nonhuman primates and, increasingly, our hominin ancestors and relatives. In this study, we describe an antemortem lesion on the root of a Paranthropus robustus third molar from Drimolen, South Africa, which likely represents another example of caries in fossil hominins. Materials and Methods: The molar, DNH 40, is dated to 2.0–1.5 Ma and displays a lesion on the mesial root surface, extending from the cementoenamel junction 3 mm down toward the apex. The position and severity of the lesion was macroscopically recorded and micro‐CT scanned to determine the extent of dentine involvement. Results: A differential diagnosis indicates root caries, as the lesion is indistinguishable from clinical examples. Although necrotic in appearance, external tertiary dentine is evident on a micro CT scan. Gingival recession and/or continuous eruption of the tooth as a result of extensive occlusal wear would have occurred to facilitate caries formation. Therefore, the lesion is likely linked to relative old age of this individual. Discussion: This new example increases the total number of carious lesions described in P. robustus teeth to 10, on occlusal, interproximal, and now, root surfaces. Beyond the consumption of caries‐causing food, caries formation would have also required the presence of requisite intraoral cariogenic bacteria in this individual and the species. Of interest, the presence of tertiary dentine on the outward surface suggests the DNH 40 lesion may have been arrested, that is, no longer active, perhaps relating to a change in diet or oral microbiome just prior to the individual's death.